A data set for mental and physical stress, loneliness, and life satisfaction before and during the COVID-19 pandemic and the role of working from home - Franziska Emmerich; Julia Junghans; Markus Zenger; Elmar Brähler; Yve Stöbel-Richter; Lisa Irmscher; Ernst Peter Richter; Hendrik Berth (BMC Research Notes)
Abstract Objectives To examine mental and physical health, loneliness, and life satisfaction in East Germany, data were collected at four time points: in 2017/2018, 2019/2020, 2021, and 2022. Changes in data before and during the COVID-19 pandemic were determined using validated short scales. Additionally, a newly developed questionnaire was integrated in 2022 to depict working from home (WFH). Data description The data set is part of the Saxon Longitudinal Study (SLS), first conducted in 1987 in the former German Democratic Republic and has been continued almost annually, consisting of 33 waves since then (N > 300). As an East German sample, the SLS offers a long-term perspective on psychological and physical health. The extent of mental health can be interpreted based on validated short scales D-Score (Distress Score), PHQ-4 (Patient Health Questionnaire-4), LS-S (Loneliness Scale), L-1 (Short Scale of Life Satisfaction), and a Corona Anxiety Scale. The physical strain can be interpreted based on the answers to the G-Score, SSS-8 (Somatic Symptom Scale), and an individual item on health status. The questionnaire on WFH allows comparisons between participants WFH and those who did not. This dataset will contribute to further research into events such as the COVID-19 pandemic and their impact.